The Past Isn’t What It Used To Be: Critical Fabulation and Remembering Revolt - Wendt Höjer, Fanny (Tidskrift för litteraturvetenskap, 2020)
Critical feminist theorists have pointed out how the idea of the singular, revolutionary Act tends to reinforce masculinist and colonialist imaginaries. In this essay, I argue for the need to elaborate other ways of revolting. Through a reading of Saidiya Hartman’s Wayward Lives, Beautiful Experiments, I explore ways to consider the relationship between embodied acts of resistance and past bodies’ gestures, as a strategy to reformulate resistance away from the single Act, often enacted by an autonomous, male subject. In Wayward Lives, Beautiful Experiments, Hartman merges archival research with fictional storytelling, giving voice to young, black women in the United States in the early 20th century. I argue that, when reading Hartman’s text through feminist ontologies of interdependency, acts of revolt appear as collective gestures, re-appearing through time, rather than as singular events. thus, this reading of Wayward Lives, Beautiful Experiments, demonstrates how we can rethink the singular Act of resistance.